Identification of Landslide-Prone Subsoil Using Wenner Configuration Geoelectric Method in Gayamharjo Village, Prambanan District, Sleman Regency - Tihurua, Najila; Niyartama, Thaqibul Fikri; Setyaningrum, Yunita Eri; Uyun, Qurrotul (Proceeding International Conference on Science and Engineering, 2019)
Landslides occur due to the field of slip. Identification of Soil Landslide Identification Using Geolistrik Method The Wenner configuration has been done in Gayamharjo Village, Prambanan Sub-district, Sleman District. This study aims to determine the structure of subsurface rocks and identify the field of ground slip in the landslide prone areas in the study area. Measurements were made as many as 3 trajectories, the smallest spaced between 20 meters electrode with 300 meters of track length. The tool used is Syscal Jr Switch-48. Data processing uses RES2DINV software that produces 2D subsurface modeling. The results of the interpretation showed that th e location of the study identified the constituent rock consisting of three layers of subsurface rocks (1,36 to 6,86) ?m, sandstone (15,4 to 34,6) ?m, and andesite rocks (77, 8 to 393) ?m. In the three trajectories of the research area, there is a slip field with th e potential for landslide: track 1 at point 40 s.d.80 with a depth of 37 m, track 2 at point 220 s.d. 240 with depth 26 m, path 3 at point 100 s.d. 140 with a depth of 37 m.